Analisis Tingkat Pendapatan dan Kesejahteraan Pelaku Usaha di Kawasan Wisata Pantai Tapaktuan Tapa Desa Pasar Kecamatan Tapaktuan Kabupaten Aceh Selatan - Jaya, Alfi Syahril Fuadi; Husna, Zumara; Irsyadillah, Irsyadillah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
General Tapaktuan Tapa Beach Tourism is one of the most visited tourist attractions in South Aceh Regency because the site is very large, namely 6 meters long and 2.5 meters wide. So, this uniqueness attracts many tourists who visit and has a big impact on businesspeople at Tapaktuan Tapa Beach Tourism. This research aims to analyze the level of income and welfare of business actors in the Tapaktuan Tapa Beach Tourism area, Pasar Village, Tapaktuan District, South Aceh Regency. This research uses a qualitative approach with descriptive research type. The respondents in this research were 3 business actors in Tapaktuan Tapa Beach Tourism. The data collection techniques used were library research and field research. In analyzing the data, the techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the existence of Tapaktuan Beach Tourism is very helpful in increasing the level of income and welfare of business actors in Tapaktuan Tapa Beach Tourism. The average income of business actors is IDR 20,300,000.00 per month. The level of welfare of business actors in Tapaktuan Tapa Beach Tourism is at the stage of financial vitality, namely the condition of someone who can meet the financial security costs and then has a small supply of funds for fun, such as buying clothes, luxury meals and entertainment